2009
DOI: 10.1007/s10964-009-9490-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Multiple Types of Child Maltreatment on Subsequent Risk Behaviors Among Women During the Transition from Adolescence to Young Adulthood

Abstract: The purpose of this study was to investigate how different types of child maltreatment, independently and collectively, impact a wide range of risk behaviors that fall into three domains: sexual risk behaviors, delinquency, and suicidality. Cumulative classification and Expanded Hierarchical Type (EHT) classification approaches were used to categorize various types of maltreatment. Data were derived from Wave III of the National Longitudinal Study of Adolescent Health (Add Health). Our sample consisted of Whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
113
4
20

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(142 citation statements)
references
References 40 publications
(59 reference statements)
5
113
4
20
Order By: Relevance
“…Our findings on sexual abuse/violence are compatible with several studies: the review findings of Devries and Seguin [28] and the study of Brezo et al [29] on child abuse in a large cohort of school children, the community study of Mullen et al [30], the review of Santa Mina et al [31], studies on bipolar patients [32][33][34] and on substance-dependent patients [35] and, lastly, the twin study of Kendler et al [36], who found that all psychiatric disorders were associated with sexual abuse. Sexual trauma is common among women, as shown by a large investigation of sexually-experienced American young women, where the prevalence rate of childhood sexual abuse (CSA) was 4.6% [37] and is more frequent among women than men [38]. In a large, nationally representative sample of 9 th grade students in Switzerland, 40.2% of girls reported having experienced at least one type of CSA event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings on sexual abuse/violence are compatible with several studies: the review findings of Devries and Seguin [28] and the study of Brezo et al [29] on child abuse in a large cohort of school children, the community study of Mullen et al [30], the review of Santa Mina et al [31], studies on bipolar patients [32][33][34] and on substance-dependent patients [35] and, lastly, the twin study of Kendler et al [36], who found that all psychiatric disorders were associated with sexual abuse. Sexual trauma is common among women, as shown by a large investigation of sexually-experienced American young women, where the prevalence rate of childhood sexual abuse (CSA) was 4.6% [37] and is more frequent among women than men [38]. In a large, nationally representative sample of 9 th grade students in Switzerland, 40.2% of girls reported having experienced at least one type of CSA event.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism whereby sexual trauma leads to suicidality seems to lie in its magnification of the concurrent experience of other forms of childhood maltreatment [37]; however, the effect of sexual trauma has also been shown to be attenuated by controlling for affective symptoms [38] and parental psychopathology [40,41]. Moreover, with respect to personality disorders it has been shown that if sexual abuse was multivariately adjusted for other forms of abuse -in particular emotional abuse and neglect -its detrimental impact became negligible [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…More often, related constructs such as low family support, family dysfunction, or childhood abuse, an extreme form of emotional invalidation, have been examined in relation to suicidal and self-injurious behavior. Numerous studies have found that childhood abuse, particularly sexual abuse, is a robust predictor of future suicidal behavior (Martin et al 2004;Calder et al 2010;Hahm et al 2010;). In addition, perception of insufficient family support has been positively correlated with adolescents' suicide attempts (Morano et al 1993;King et al 1995;Groholt et al 2000) and suicidal patients have been found to report lower levels of family support and parental affection and engagement than nonsuicidal inpatients and adolescents from the community (King et al 1993;Morano et al 1993;Groholt et al 2000).…”
mentioning
confidence: 99%
“…Classifying the presence of violent interpersonal conduct overlooks evidence indicating that different types of maltreatment produce different effects on psychosocial health (Hahm, Lee, Ozonoff, & Van Wert, 2010;Teicher et al, 2006) and that co-occurring maltreatment types effects the well-being of children and adolescents differently (Hazen, Connelly, Roesch, Hough, & Landsverk, 2009;Villodas et al, 2012). For example, Berzenski and Yates (2011) identified subgroups of emerging adults based on multiple indicators of maltreatment, and found significant subgroup differences across a number of psychosocial outcomes.…”
Section: Focusing On the Presence Of Violencementioning
confidence: 99%